2019
DOI: 10.1017/s0022215119000215
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after total laryngectomy: evaluating the effect of socioeconomic status

Abstract: ObjectiveTotal laryngectomy is considered the primary treatment modality for advanced laryngeal carcinoma. This study assessed the quality of life in patients after total laryngectomy, and ascertained whether quality of life is affected by socioeconomic status.MethodForty-seven patients (20 state- and 27 private-sector) who underwent total laryngectomy between 1998 and 2014 responded to the University of Washington Quality of Life Questionnaire, the Voice-Related Quality of Life Questionnaire and the Brief Ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
(31 reference statements)
3
9
0
Order By: Relevance
“…In total, eight studies reported on the UW-QOL. 12,[47][48][49][50][51][52][53] A majority of studies presented mean scores reaching the MCID threshold when compared with the normative reference data in most domains, except pain, saliva, and anxiety. In these three domains, between a quarter and a third of studies presented a mean score reaching the MCID threshold (Fig.…”
Section: Uw-qolmentioning
confidence: 98%
“…In total, eight studies reported on the UW-QOL. 12,[47][48][49][50][51][52][53] A majority of studies presented mean scores reaching the MCID threshold when compared with the normative reference data in most domains, except pain, saliva, and anxiety. In these three domains, between a quarter and a third of studies presented a mean score reaching the MCID threshold (Fig.…”
Section: Uw-qolmentioning
confidence: 98%
“…We conducted a study to examine whether QoL after laryngectomy is affected by socioeconomic status, and whether potential laryngectomy patients should be counselled differently depending on their socioeconomic status. 17 Specifically, we carried out a cross-sectional, observational QoL assessment of public (Groote Schuur Hospital) versus private patients, more than two years after laryngectomy. Quality of life was measured using the Updated University of Washington Quality of Life questionnaire, the Voice-Related Quality of Life questionnaire and the Brief Illness Perception questionnaire.…”
Section: Does Socioeconomic Status Affect Quality Of Life After Total Laryngectomy?mentioning
confidence: 99%
“…; 15,16 and ( 7) does socioeconomic status affect QoL after total laryngectomy? 17,18 Does tracheostomy cause peristomal recurrence?…”
mentioning
confidence: 99%
“…However, most of these studies use a single questionnaire, or they apply one specific voice and one specific cancer to assess different forms of rehabilitation when more than one are associated (9,(10)(11)(12)(13)(14)(15)(16). Previous studies have compared different instruments for monitoring quality of life after cancer treatment but without detailing the variable of phonatoric rehabilitation (17)(18)(19). The Voice Handicap Index (VHI) (20) and Voice-Related Quality of Life (V-RQOL) (21) are among the quality of life instruments most widely used by voice specialists.…”
Section: ' Introductionmentioning
confidence: 99%
“…Some studies have applied UW-QOL to investigate individuals who have undergone total laryngectomy (19,16), to compare quality of life between a group of total laryngectomized individuals and a group of individuals who underwent organ preservation treatment (31) or for the comparison among tracheoesophageal prosthesis, oesophageal voice or electronic larynx (16).…”
Section: ' Introductionmentioning
confidence: 99%